2020
DOI: 10.1371/journal.ppat.1008740
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I RNA editing in bacteria increases pathogenicity and tolerance to oxidative stress

Abstract: Adenosine-to-inosine (A-to-I) RNA editing is an important posttranscriptional event in eukaryotes; however, many features remain largely unexplored in prokaryotes. This study focuses on a serine-to-proline recoding event (S128P) that originated in the mRNA of fliC , which encodes a flagellar filament protein; the editing event was observed in RNA-seq samples exposed to oxidative stress. Using Sanger sequencing, we show that the S128P editing event is induced by H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 76 publications
1
62
0
Order By: Relevance
“…A recent report linked a specific A-to-I editing event on the mRNA of the flagellar filament protein fliC to an increased virulence in the bacterial plant pathogen Xanthomonas oryzae pv. oryzicola ( Xoc ) ( Nie et al, 2020 ). Plants often generate ROS as a defensive reaction to either directly kill invading pathogens or, more importantly, work as signaling molecules for gene expression activation in the context of pathogen defense ( Torres et al, 2006 ; Paiva and Bozza, 2014 ).…”
Section: The Transcribed Mrna Is Translated To Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report linked a specific A-to-I editing event on the mRNA of the flagellar filament protein fliC to an increased virulence in the bacterial plant pathogen Xanthomonas oryzae pv. oryzicola ( Xoc ) ( Nie et al, 2020 ). Plants often generate ROS as a defensive reaction to either directly kill invading pathogens or, more importantly, work as signaling molecules for gene expression activation in the context of pathogen defense ( Torres et al, 2006 ; Paiva and Bozza, 2014 ).…”
Section: The Transcribed Mrna Is Translated To Proteinsmentioning
confidence: 99%
“…The authors identified a serine to proline mutation (S128P) in FliC after exposing the bacteria to H 2 O 2 . The S128P editing event can potentially change filament structure and enhance biofilm formation, leading to an increased oxidative stress tolerance ( Nie et al, 2020 ).…”
Section: The Transcribed Mrna Is Translated To Proteinsmentioning
confidence: 99%
“…To deal with oxidative stress, bacterial pathogens often deploy enzymes that either tolerate or scavenge ROS. We recently demonstrated that adenosine-to-inosine (A-to-I) RNA editing in Xoc increased tolerance to H 2 0 2 [ 20 ]. A-to-I editing in the target fliC caused structural changes in flagella that increased biofilm formation and ultimately improved ROS tolerance [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that adenosine-to-inosine (A-to-I) RNA editing in Xoc increased tolerance to H 2 0 2 [ 20 ]. A-to-I editing in the target fliC caused structural changes in flagella that increased biofilm formation and ultimately improved ROS tolerance [ 20 ]. A number of studies have shown that sRNAs can also regulate tolerance to oxidative stress in prokaryotes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation